Keindahan Sentuhan Tafsir Qusyairi Dalam Menafsirkan Syukur - Hakim, Luqmanul; Rambe, Uqbatul Khoir (Jayapangus Press, 2025)
The concept of gratitude in Islamic teachings occupies an important position in shaping spiritual awareness and ethical values in the lives of the faithful, especially when examined through the perspective of Sufi interpretation. The meaning of gratitude is not limited to verbal expressions of divine gifts, but encompasses an inner dimension that reflects internal acknowledgment, expressions of praise, and the application of blessings in tangible actions. This study aims to examine how the verses of gratitude are interpreted in Tafsir al-Qusyairi, a tafsir work that highlights the isyāri approach and deepens the spiritual aspects of the Qur'an. The approach used is descriptive-qualitative through literature study, emphasizing thematic analysis of the word